Occupational Safety and Health Education for Indonesian Migrant Workers (PMI) - Evi Widowati; Margareta Rahayuningsih; Risa Anggita Putri; Hanif Satria Febriananda; Aza Putri Anisa; Ayu Fadilah Wahid; Yoris Adi Maretta (Jurnal Pengabdian UntukMu NegeRI, 2024)
The large number of Indonesian Migrant Workers (PMI) requires protection of Occupational Safety and Health (OSH) which is the human right of every worker. However, in practice there are still many OSH problems among PMI in South Korea, including: work accidents, violence, problems related to work legality, and PMI's knowledge regarding OSH implementation and norms is still very minimal, therefore the aim of this activity is to provide education through training and discussions related to aspects of OSH which include efforts to prevent work accidents and implementation of work norms. The method for implementing this activity includes: 1) preparation stage, 2) implementation stage and 3) evaluation stage. This activity has received an ethical certificate no. 315/KEPK/FK/KLE/2024 from the Health Research Ethics Commission, Faculty of Medicine, UNNES. The results of this activity can be seen that PMI is very enthusiastic about participating in this activity and states that this activity is very beneficial for them, especially in increasing their knowledge regarding the application of OSH aspects in the workplace which is not only useful for preventing work accidents but also improving their work productivity.